Diagnosis of the reality of the dimensions of job maturity in the private universities (a survey of the views of the directors and executives at the University of Noroz) - Othman, Hilovan H. (Academic Journal of Nawroz University, 2019)
This research seeks to diagnose the reality of the University's dependence on the dimensions of functional maturity. In order to reach this goal, the number of employees in the university faculties was chosen to be a sample of the current research. As for the nature of data collection method, (40) of which 35 were valid for analysis and statistical programming (SPSS V.11.5) was used to analyze the search data. A number of results, including the University Researched by adopting the dimensions of career maturity different precedence according to their importance for the sample surveyed, The dimensions of career maturity (b crystallize trends on the work, and the ability to make decisions, career planning, the ability to excel, and job training). This research presented a number of recommendations, the most important of which is the necessity of providing the university with the desired maturity in its main dimensions in the course of its career. It represents the best way to ensure excellence in them so that they can overcome the difficulties and solve the dilemmas.